2018
DOI: 10.1186/s12889-018-6099-9
|View full text |Cite
|
Sign up to set email alerts
|

Injuries among young workers in career-technical-vocational education and associations with per pupil spending

Abstract: BackgroundNew Jersey Department of Education (NJDOE) requires by law for accidents/incidents (injury) involving career-technical-vocational education (CTE) students and staff to be reported within five business days to the NJ Safe Schools Program (NJSS) using an online surveillance system. NJ public schools and charter schools (CS) through school districts (SD) or county offices report school data annually to NJDOE, including per pupil spending (PPS). In this study, we examined potential associations of PPS wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Detailed descriptive and other statistics from the NJ SS online injury surveillance system (New Jersey Safe Schools Program. Incident Reporting, 2019) for the present study’s time period appear elsewhere in references cited (Shendell et al, 2010; Shendell et al, 2012a; Shendell et al, 2012b; Rubenstein et al, 2014; Apostolico & Shendell, 2016; Shendell et al, 2018). One hundred fourteen youth fatalities were identified from 1990 to 2016 through the NJ Fatal Occupational Injuries Surveillance project.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Detailed descriptive and other statistics from the NJ SS online injury surveillance system (New Jersey Safe Schools Program. Incident Reporting, 2019) for the present study’s time period appear elsewhere in references cited (Shendell et al, 2010; Shendell et al, 2012a; Shendell et al, 2012b; Rubenstein et al, 2014; Apostolico & Shendell, 2016; Shendell et al, 2018). One hundred fourteen youth fatalities were identified from 1990 to 2016 through the NJ Fatal Occupational Injuries Surveillance project.…”
Section: Resultsmentioning
confidence: 87%
“…Details of the NJ SS online injury surveillance system, which covers secondary school students ages 14–21 in NJ approved CTE programs, are available online (New Jersey Safe Schools Program. Incident Reporting, 2019) as well as references cited (Shendell et al, 2010; Shendell et al, 2012a; Shendell et al, 2012b; Rubenstein et al, 2014; Apostolico & Shendell, 2016; Shendell et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly injured body parts had been hands, fingers, and legs .The most commonly reported injury kind was cuts/lacerations. Moreover, the study revealed that these injuries have been due to lack of knowledge about occupational fitness and safety (15) .…”
Section: Introductionmentioning
confidence: 99%